PERSEPSI RESIMEN MAHASISWA (MENWA) TERHADAP WAJIB MILITER DALAM RANGKA PERTAHANAN NEGARA (StudipadaResimenMahasiswaUniversitasGadjahMadadanUniversitas Indonesia) - , SITI FADILAH; , Prof. Dr. Sudaryono, SU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study, which is entitled the perception of student regiments of the conscription in the context of state defence, aims at finding out the student regiments' perception of the conscription and the factors promoting it as well as the strategy of conscription in Indonesia. This study uses survey method with quantitative descriptive analysis approach. The author examines the student regimentsâ perception of the conscription in the framework of national defense, case study on the student regiments in the University of Gadjah Mada and in the University of Indonesia. The study reveals that, based on the perception of the student regiments, the compulsory military service certainly needs to be enforced in Indonesia, as the country is having insufficient main componentsfor defense. The factors contributing to the enforcement of conscription in Indonesia isthe nationalism spirit, the presence of threat to the country and the need to protect its natural resources from other countries. Meanwhile, according to the student regiments, the appropriate conscription strategy should be enforced for Indonesian citizens aged from 19 to 30 years old, with the duration of services ranging from 3 or 4 months up to 1 year in the form of military and morale trainings. The study concludes that thestudent regiment,as a young generation that plays a strategic role, has a perception that conscription needs to be enforced even though it is not direly needed. The enforcement of compulsory military service may be driven by several factors, among which are nationalism and threats.